Efektivitas Pembelajaran Berdiferensiasi Berbantuan Articulate Storyline 3 dalam Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Putri Febriyanti, Melisa; Humairo, Nur; Rahmawati, Pebriani; Karlingga, Like Dewi; Maghfiroh, Imarotul; Afifah, Nabila Tazkiyyatul; Alhidayah, Nila; Irianto, Apri; Zulfiatus Sholichah, Laila (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to analyze the application of differentiated learning assisted by Articulate Storyline 3 media in improving mathematics learning outcomes of class IIIA students at SDN Kebraon II Surabaya. The main problem faced is the low interest and learning outcomes of students in mathematics subjects, so that innovative learning strategies are needed and in accordance with the individual needs of students.Method – This study employed a Classroom Action Research (CAR) method with two cycles conducted in SDN Kebraon II Surabaya. Data was collected through learning outcome tests. Data analysis was conducted using descriptive quantitative methods to observe improvements in student learning outcomes from the pre-cycle to cycle 2, complemented by Wilcoxon Signed Rank Test to assess statistical significance. Findings – The results showed that the application of differentiated learning assisted by Articulate Storyline 3 can improve student learning outcomes. The student’ average score increased from 51.92 (pre-cycle) to 70 (cycle 1) and 83.02 (cycle 2). The Wilcoxon Signed Rank Test revealed significant differences between pre-cycle and cycle 1 scores (p = 0.000 ? 0.05), as well as between cycle 1 and cycle 2 scores (p = 0.000 ? 0.05), confirming a statistically significant improvement. Research Implications – This study suggests that teachers should integrate interactive media Articulate Storyline 3 in differentiated learning to enhance engagement and learning outcomes. However, this study was limited to a small sample size of 26 students, and further research is needed to explore long-term effects on different student demographics.